PENGARUH MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP SISWA TENTANG CUCI TANGAN PAKAI SABUN DI SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2021)
CTPS behavior is one of the Clean and Healthy Behaviors in dealing with germs and can reduce the risk of infectious diseases. The results of this study were motivated by the incidence of diarrhea in the working area of the Babakan Sari Health Center UPT, the largest area of diarrhea handling coverage in the all age category was in the Panyileukan sub-district 117.90%, Astana Anyar 107.31%, and Kiaracondong 101.29%. This study aims to analyze the effect of video media on students' knowledge and attitudes about hand washing with soap at SDN 158 Babakan Sari, Bandung City. The research design used is quantitative research with the one group pretest posttest method, which is to measure the effect of video media on students' knowledge and attitudes about washing hands with soap. From the pretest-posttest questionnaire of attitudes and knowledge, data processing was carried out by using the Wilcoxon signed test. The results of this study indicate that knowledge and attitudes through the provision of education in the form of videos to 71 students increased. Based on the analysis test conducted, a significant value on knowledge before and after being given a video intervention was 0.043 <0.005, and the results of research on attitudes before and after being given a video intervention was 0.002 <0.005, so it can be concluded that there is a significant effect of providing health education in the form of video. on increasing the knowledge and attitudes of 5th graders at SDN 158 Babakan Sari, Bandung City. The media that has been created can be reused or disseminated to provide education to students, especially SDN 158 Babakan Sari.